Who owns Britain? : the story of the ordinary man and women, unwanted in peace, whose skill, courage and sacrifice saved Britain in war : the story of the financiers and monopolists who made a Britain of distressed areas and unemployment, and who are fighting to preserve their power - Schaffer, Gordon (Manchester : Co-operative Press, 1945)
Bibliotheek Camille Huysmans
Herdruk gebaseerd op artikels in 'Reynolds News'
Engels
Monografie
Keywords: Wereldoorlog 2; economische politiek; arbeidersbeweging; Groot-BrittanniÃ«.